Investigation of the effect of debridement combined with antibiotic-loaded bone cement on pain and psychological status in diabetic foot ulcer patients - Yang, Ke; Huang, Yijun; Zhang, Yinxu; Wen, Yin; Yan, Linjie; Chen, Wei; Wei, Zairong; Nie, Kaiyu (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to investigate the changes in pain levels and psychological status in patients with diabetic foot ulcers (DFUs) after accepting the debridement combined with antibiotic-loaded bone cement (ALBC), which offers insight into a comprehensive treatment including pain management and psychological intervention with DFUs.MethodsWe conducted a retrospective analysis of 103 patients with DFUs meeting the inclusion criteria at a tertiary academic hospital, divided into pain group (n = 61) and numbness group (n = 42), anxiety group (n = 67) and non-anxiety group (n = 36), and depression group (n = 16) and non-depression group (n = 87). All patients were assessed pain levels and psychological status with brief pain inventory (BPI) and hospital anxiety depression scale (HADS) before and after debridement combined with ALBC.ResultsThe primary outcomes were that pain degree score, pain-related impact score, and anxiety score of the depression group were higher than those of the non-depression group (p < 0.001). The total scores of pain severity and pain-related effects in the pain group decreased after debridement combined with ALBC (p = 0.001, p < 0.001), but these scores were always higher than those of the no-pain group (p < 0.001). Moreover, the anxiety and depression scores also decreased in most patients who also had a good wound-healing process (p < 0.001).ConclusionThese findings suggest that debridement combined with ALBC of DFU patients may be associated with alleviation of pain and improvement in psychological status in various aspects including controlling infection, promoting wound healing, and reducing frequent treatment, as a recommendation for the widespread therapy used in the clinical treatment of DFUs.